Political Environment and Implementation of Public Private Partnership Infrastructure Development in Kenya - Baithili, Moses K.; Mburugu, Kirema Nkanata; Njeru, Duncan Mugambi (European Scientific Journal, ESJ, 2019)
Public Private Partnership (PPP) is a long term agreement between the public and private sector where risks and rewards are shared in developing a public facility. Private sector play a monumental role in bridging public finance deficit on capital projects. In Kenya, the government has created an enabling environment for private sector participation in the country’s infrastructure development which is meant to spur economic growth. This study sought to establish the effect of political environment on the implementation of Public Private Partnership infrastructure development projects in Kenya. The cross-sectional descriptive survey research methodology was used in the study. The population of the study was sixtythree PPP projects being implemented in Kenya across different sectors. One project was used in pretesting of research instruments. Therefore, the actual population used in the study was sixty-two projects. The study adopted systematic sampling technique where the first n th element was randomly selected. A sample size of 31 was selected from the sampling frame using sampling fraction. Questionnaires were administered to procurement officers charged with implementation of PPPs in the sampled organizations. To ensure validity of the data, the research questionnairre was verified by experts made up of the research supervisors. The research instruments were pretested during pilot study. Qualitative data was analyzed and presented through descriptions while the quantitative data was analyzed using descriptive statistics, measures of central tendency, measures of dispersion and inferential statistics. Multiple regression analysis was used to determine the relationship between dependent and independent variables. The study found that most of the organizations were in the initial stages of implementation of PPPs. The majority of the respondents considered the political environment in Kenya unstable because of the disputed presidential elections which was happening at the time the data was collected. The study also found political environment had significant influence on the implementation of PPPs in Kenya. The respondents also identified corruption, poor project selection, lack of experts and cost over-runs as other factors that affected implementation of PPPs. The results of the study will inform policy makers in public entities, County and National Governments to put in place necessary mechanisms to manage politics and fight corruption to increase uptake of Public Private Partnership for infrastructure development in Kenya.